Embedding Effects in the OECD Better Life Index - Louisa von Reumont; Ronnie Schöb; Clemens Hetschko (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The OECD aims to foster `better policies for better lives'. To this end, the OECD invites people to evaluate quality-of-life indicators according to their individual preferences, using the web-based Better Life Index. These indicators are embedded in 11 broader well-being dimensions. Our experiment shows that this procedure yields strong embedding effects, casting serious doubts on the reliability of the Better Life Index as well as its usefulness in providing meaningful policy recommendations.
Keywords: B41; C42; I31; 330